New Integration Period? Changing Tendencies of the Urban Network in South East Europe - Szilárd Rácz (DETUROPE)
The past two decades have brought basic changes in the whole Balkan Peninsula, where spatial structures and settlement network were not devoid of changes either. Due to the change of the economic, political and social regime and the new borders spatial structures became differentiated along new factors. Cooperation programs of the Euro-Atlantic integration hold many new challenges and opportunities. Historical and political literature studying the single countries’ transformation is large and far reaching, however, a settlement network and spatial structure focused overview has been, so far, missing from the range of researches. The aim of this study is to examine the urban features and the spatial transition of the Balkan states.